2020
DOI: 10.3389/fmicb.2020.569512
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promoting Rhizobacteria Alleviate Aluminum Toxicity and Ginger Bacterial Wilt in Acidic Continuous Cropping Soil

Abstract: Long-term monoculture cropping is usually accompanied by soil acidification and microbial community shifts. Soil aluminum ions are dissolved under acidic condition (pH < 5.0), and the resulting aluminum bioavailability can cause toxic effects in plants. In this study, we investigated the bacterial community compositions and aluminum toxicity in fields monocultured with ginger for 35 years, 15 years, and 1 year. Within these fields are ginger plants without and with ginger bacterial wilt disease. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Soil microbial community structure affects plant health and can also be used as an indicator of soil health ( Zhou and Wu, 2012 ; Dong et al, 2016 ). High-throughput sequencing analysis showed that long-term continuous cropping could reduce soil bacterial biomass and increase fungal biomass ( Dong et al, 2016 ; Liu et al, 2016 , 2020a ), while longer-term continuous cropping could increase the bacterial diversity to suppress soil-borne diseases by forming bacteriostatic soil ( Shen et al, 2018 ; Zhang et al, 2020 ). Studies have shown that the higher the ratio of bacterial to fungal in soil, the better condition of the soil ecosystem, the more stable the structure of bacteria, and the stronger the resistance of soil to disease ( Liu et al, 2015a , b ).…”
Section: Evolutions Of the Assembly Of Soil Microbial Community Drove...mentioning
confidence: 99%
See 2 more Smart Citations
“…Soil microbial community structure affects plant health and can also be used as an indicator of soil health ( Zhou and Wu, 2012 ; Dong et al, 2016 ). High-throughput sequencing analysis showed that long-term continuous cropping could reduce soil bacterial biomass and increase fungal biomass ( Dong et al, 2016 ; Liu et al, 2016 , 2020a ), while longer-term continuous cropping could increase the bacterial diversity to suppress soil-borne diseases by forming bacteriostatic soil ( Shen et al, 2018 ; Zhang et al, 2020 ). Studies have shown that the higher the ratio of bacterial to fungal in soil, the better condition of the soil ecosystem, the more stable the structure of bacteria, and the stronger the resistance of soil to disease ( Liu et al, 2015a , b ).…”
Section: Evolutions Of the Assembly Of Soil Microbial Community Drove...mentioning
confidence: 99%
“…Some bacteria, which belong to plant growth promoting rhizobacteria (PGPR), can secrete antibiotics to inhibit pathogenic microorganisms. Still, continuous cropping reduces bacteria-secreted antibiotics ( Zhang et al, 2020 ) and the inhibition of pathogenic bacteria ( Tan et al, 2017 ) and then causes an increase in plant diseases incidence. Meanwhile, the secondary metabolites secreted by harmful microorganisms recruit microorganisms that are beneficial to themselves, further damaging the soil microecology, evolving in a direction conducive to the survival of those, and aggravating the obstacles of continuous cropping ( Chen et al, 2018a ; Pascale et al, 2019 ; Bakker et al, 2020 ).…”
Section: Evolutions Of the Assembly Of Soil Microbial Community Drove...mentioning
confidence: 99%
See 1 more Smart Citation
“…When plants are in a stressful environment, root exudates can attract beneficial microbes from the environment, which is called a “cry for help” strategy ( 65 ). Aluminum stress can stimulate the increase of Bacillus and Pseudomonas to alleviate ginger aluminum toxicity and bacterial wilt in extremely acidic soil (pH less than 4.5) ( 7 ). In this study, in a high-aluminum soil environment with pH 4.45, the growth of tobacco was not significantly affected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At pH 4.5 or below (extremely acid), the Al 3+ predominates in the soil solution and has the greatest impact on plant growth ( 5 ). In addition, many researchers revealed that soil acidification is closely related to the occurrence of soilborne disease ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%